Penerapan Teori Keadilan dalam Putusan Harta Bersama (Analisis Perkara Nomor 0346/Pdt.G/2017/PA.Ktb) - Muhammad Nafi; Citra Mutiara Solehah (Jurnal Hadratul Madaniyah, 2020)
Justice in the decision of a case is the main objective of the trial process carried out. The theories of justice written by experts must have been understood by the judge. In the case of a joint property suit, it is necessary to apply the methods of justice by the judge in deciding the case. Although the regulations governing shared assets are divided into half each, in reality, there are proven legal facts in the trial to conduct contra legem. However, in the decision of the Kotabaru Religious Court Number 0346/Pdt.G/2017/PA.Ktb, although it was evident that the joint property, which was one of the sources of income from the Plaintiff and Defendant in his life, was entirely controlled by the Defendant since the separation from the Plaintiff. The Plaintiff even had to pay more for his livelihood because he had to live and earn a living outside the joint property. The Panel of Judges decided that the joint property was divided in half each to the Plaintiff and Defendant. This has become a problem in the application of the theory of justice that takes into account the Plaintiff's contributions and losses in the joint venture. This study aims to describe how the legal considerations of the judges, and their relationship with the theory of justice used by the Panel of Judges.